Aesthetic Values and their relationship to Critical Thinking in a sample of female students of King Abdul Aziz University - Alshehabi, Amera Muhmmed (Journal of Educational and Psychological Sciences, 2021)
The study aims to know the effect of aesthetic values on critical thinking among students of King Abdul Aziz University. This study sample consisted of (282) female students, (159) from literary specialties while (123) were from scientific specialties. The researcher used the descriptive correlative approach, and the study tools have consisted of aesthetic values scale done by the researcher, the test of critical thinking prepared by Watson & Glasser (1980). The results of the study showed that there was no statistically significant relationship between aesthetic values and critical thinking at level (0.05≥α) in the study sample. The results also showed that there were no statistically significant differences in the mean scores of the participants in the study among the aesthetic Values. While there is partly differences among critical thinking variable.